1993
DOI: 10.1002/mrm.1910290603
|View full text |Cite
|
Sign up to set email alerts
|

Resolution of phospholipid molecular species by 31P NMR

Abstract: Phosphorus-31 NMR chemical shifts of phospholipids (PLs) solubilized in bile salts were studied with respect to variations in the structure of the acyl substituents. The presence of double bonds in the acyl chains of phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylglycerol (PG), and phosphatidic acid (PA) induced small but consistent upfield shifts relative to the corresponding disaturated acyl PL signals. The magnitudes of the unsaturation-related upfield shifts were approximately twice a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…For example, 16:0/15Ј-HPETE-PC refers to the derivative of 16:0/20: 4-PC with a hydroperoxy group at C-15 of the sn-2 acyl substituent (20:4 ϭ ETE ϭ eicosatetraenoic acid) and a double bond at the C-13,14 position due to migration of the double bond originally at C-14,15 into conjugation. Quasispecies format: A partial sorting of species by 31 P NMR chemical shift (␦) occurs in the PL ad system (see below) (12), providing structural information intermediate between the species and headgroup class levels. Groupings are represented by two-letter prefixes.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, 16:0/15Ј-HPETE-PC refers to the derivative of 16:0/20: 4-PC with a hydroperoxy group at C-15 of the sn-2 acyl substituent (20:4 ϭ ETE ϭ eicosatetraenoic acid) and a double bond at the C-13,14 position due to migration of the double bond originally at C-14,15 into conjugation. Quasispecies format: A partial sorting of species by 31 P NMR chemical shift (␦) occurs in the PL ad system (see below) (12), providing structural information intermediate between the species and headgroup class levels. Groupings are represented by two-letter prefixes.…”
Section: Methodsmentioning
confidence: 99%
“…The signal from 16:0/16:0-PC furnished a convenient internal chemical shift reference due to its ubiquity, ease of resolution, and previous correlation with the standard 31 P NMR zero shift reference, 85% H 3 PO 4 (10,12,18). A PC shift near Ϫ0.5 ppm, although not a consensus value in the 31 P NMR literature, has been obtained using a variety of approaches (18,19).…”
Section: Chemical Shift Referencingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ach2GroPCho) and that of the monounsaturated species (e.g. Ole,GroPCho) being located at peak 9 (Pearce and Komoroski, 1993). PtdCho species containing polyunsaturated acyl chains, such as SteA,AchGroPCho gave peak 10.…”
Section: 'P-nmr Analysis Of Cellular Lipids From Human Neutrophilsmentioning
confidence: 97%
“…It has also been utilized for studying the effects of cholesterol on the fluidity of human gallbladder bile as well as for quantifying micellar PTC concentrations [61,62] . 31 P NMR spectroscopy has been used to quantify phospholipids in red cell membranes and in model bile salts [63] . Such 31 P MRS studies have shown higher concentrations of PTC and Pi in gallbladder bile compared to canalicular bile [64] .…”
Section: Bile Physiology By Mrsmentioning
confidence: 99%